Perbandingan Penurunan Elastis Fondasi Tiang Pancang dengan Menggunakan Metode Analitis dan Metode Elemen Hingga - Ningsih, Alia Adisetia; Setiawan, Agustinus Agus (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2023)
The foundation is part of the lower structure that functions to transmit the superstructure load to the soil base which is strong enough to support it and is usually dominated by the allowable settlement limit, in order to avoid danger to the superstructure. This study aims to analyze the bearing capacity and settlement of driven pile using analytical methods and Finite Element Method using Plaxis software. This study compares variations settlement and axial bearing capacity of piles with 300 mm, 400 mm, and 500 mm diameter. Based on the results obtained, the bearing capacity of the driven pile with plaxis is 20.25 – 26.63% higher than the calculation using the Schmertmann method. In terms of settlement, the results obtained are 3.37 mm for the D 300 mm, 3.29 mm for the D 400 mm, and 3.21 mm for the D 500 mm. All three settlement are still within safe limits.